Conceptual Embodiment of Values and Antivalues in the Popular Scientific Discourse in the Field of Information Technology as a Way of Actualization the Professional Axiological Picture of the World - A. Yu. Bagiyan; A. R. Arakelova (Научный диалог)
The article is devoted to the modern English-language written popular scientific discourse in the field of information technology. It is understood as a combination of texts in popular science and journalistic sources, the subject of consideration of which is information technology. This discourse is investigated in the aspect of its axiological loading and professional conditioning. A linguo-axiological, pragmacognitive and socioculturological analysis of texts from leading English-language magazines and newspapers is carried out, the materials of which include articles on information technology and aimed at a general reader. The question is raised about the relationship between the professional picture of the world, language and the value and antivalue concepts embodied with it. The discursive-pragmatic opposition of these entities is established. Attention is paid to the definition of language structures and means by which axiological concepts are verbalized, and the systematization of identified concepts is proposed. The relevance of the study is due to both the penetration of technology into all spheres of life and the features of modern communication caused by this, as well as the potential of a written popular scientific discourse to exert a speech effect on the recipients of texts. The novelty of the study is seen in filling the theoretical vacuum in the field of analysis of the most important focuses specific to a particular professional community, and ways of linguistic actualization of these focuses in texts on information technology.